In situ clinical evaluation of a stabilised, stannous fluoride dentifrice. (March 2014) - Bellamy, Philip G.; Harris, Robin; Date, Robert F.; Mussett, Andrew J. S.; Manly, Andrew; Barker, Matthew L.; Hellin, Nicola; West, Nicola X.
Abstract : Objectives: To compare the erosion protection efficacy of a stabilised, stannous fluoride (SnF2 ) dentifrice versus a sodium fluoride (NaF) dentifrice using a modified in situ clinical model. Methods: This study, a randomised parallel group in situ design with in vivo product use and ex vivo acid challenge, compared: A, a dentifrice containing 1, 450 ppm F as NaF; B, a dentifrice containing 1, 450 ppm F (1, 100 ppm F as SnF2 + 350 ppm F as NaF); and T, tap water. Sample size was n = 4 per group (total of 12 subjects) and within each subject appliances were placed on each side of the mouth (left and right). Enamel specimens were placed in different positions of the mouth (front, mid‐front, mid‐rear, rear) in each appliance (total = 8 specimens per subject). Product treatment was twice per day (lingual brushing for 30 seconds followed by swishing for 90 seconds with the resultant product/saliva slurry) in vivo for 15 days, and ex vivo acid treatment (0.02 m citric acid 5 minutes four times per day; total exposure time = 300 minutes). Data were analysed using a general linear repeated measures model with treatment, side and position as fixed effects. Within subjects, correlations were modelled assuming a different correlation and variance for treatment B relative to the other groups. Pairwise treatment differences were performed using a 5% two‐sided significance level. Results: Enamel loss (in μm) was significantly lower ( P < 0.005) for treatment B versus treatments A and T. Treatment B reduced enamel surface loss by 86.9% relative to treatment A. There was no statistical difference in mean enamel loss ( P = 0.51) between treatments A and T. Enamel loss was not statistically different for side (left vs . right; P = 0.44) or position (front, mid‐front, mid‐rear, rear; P = 0.36). Conclusion: This modified in situ erosion model confirmed the enhanced erosion protection benefits of a stabilised SnF2 dentifrice versus a conventional NaF dentifrice, validating the ability of the model to safely and effectively demonstrate differences in the erosion protection potential of oral care products.